2010
DOI: 10.2478/s11687-010-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations of the nematode communities in a hop garden soil

Abstract: A study on the seasonal fluctuation of nematode population was conducted during three vegetation periods (2005 – 2007), at 20 and 40 cm soil depth, from May to October, in a hop garden at Nemšová (Slovak Republic). The seasonal fluctuation of the nematode population was related to temperature and rainfall. At 20 cm soil depth of each year, the largest nematode population was recorded in July, and the smallest from July to October. At 40 cm soil depth, nematode abundance was not significantly different between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Nevertheless, the dominant genera were different. In Slovakia, the genus Rhabditis was the most dominant bacterial feeding nematodes which were further confirmed by Renčo et al (2010a), whereas in Moravia and Bohemia hop gardens the most dominant bacterivore was Acrobeloides. The prevalence of bacterial feeders and plant parasitic nematodes were observed in other agroecosystems as well (Bouwman & Zwart, 1994;Renčo & Valocká, 2002).…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Nevertheless, the dominant genera were different. In Slovakia, the genus Rhabditis was the most dominant bacterial feeding nematodes which were further confirmed by Renčo et al (2010a), whereas in Moravia and Bohemia hop gardens the most dominant bacterivore was Acrobeloides. The prevalence of bacterial feeders and plant parasitic nematodes were observed in other agroecosystems as well (Bouwman & Zwart, 1994;Renčo & Valocká, 2002).…”
Section: Discussionmentioning
confidence: 56%
“…The ability to feed on various food sources, positive reaction to increasing food source and small body size, should be the most important features for explanation of the rich distribution of genus Microdorylaimus through the whole soil profile in our investigated hop gardens. Renčo et al (2010a) established that decreasing abundances of the majority of omnivores and predators during the July were positively correlated with decreasing precipitation and high temperatures. Omnivores and predators have great sensitivity to disturbances (Bongers et al, 1991;Brmež et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genus Rhabditis was markedly eudominant in May and represented almost 80 % of all nematodes, but in September or July its abundance achieved only 8.5 % or 7.8 % of total nematode fauna. Renčo et al (2010) found the highest abundance of Rhabditis in hop-field in June and Venette and Ferris (1997) observed the increase of bacterial feeding nematodes at higher temperature. On the other hand, dominance of C. persegnis, Aphelenchoides minimus, Bitylenchus dubius increased during the season.…”
Section: Methodsmentioning
confidence: 99%